Team building : proven strategies for improving team performance - Dyer, W. Gibb, Jr., 1954- (Jossey-Bass, A Wiley Imprint, 2013)
Provides the knowledge and skills needed to create effective and high-functioning teams using the Four Cs framework: Context, Composition, Competencies, and Change. Also covers cross-cultural teams within the organization and leading innovation teams in today's changing environments.- Resumé vydavatel
William G. Dyer appeared as the first named author on the earlier ed.
Keywords: týmová práce; organizační změna; team work; organizational change; elektronické knihy; příručky; electronic books; handbooks and manuals